PESAN PERSUASIF IKLAN LAYANAN MASYARAKAT "KITA SIAP BELAJAR OPTIMAL!" KEMENTERIAN PENDIDIKAN KEBUDAYAAN DAN TINGKAT RESILIENSI ORANG TUA (Survei Pada Orang Tua Siswa SDN Klender 03) - Maulida Alchoirunisa (2022)
The new policy of Face-to-Face Learning in the education area is an effort by government to reduce the risk of children's psychosocial effect to the potential of learning loss. Face-to-Face of course need a support from parents which in reality still controversial until The Ministry of Education and Culture of Indonesia Republic disseminated a Public Service Announcement (PSA) called "Kita Siap Belajar Optimal!" that was made to increase resilience in the form of positive adaptive acts by parents in order allowing students to attend Face-to-Face Learning. This study aims to represent and proving the impact of parental characteristic and persuasive message of "Kita Siap Belajar Optimal!" toward the level of parental resilience by testing persuasive communication theory. Method that used in this study is explanative survey by disseminate online questionnaires to 268 student's parents at SDN Klender 03 as a research sample that chosen using proportional random sampling. The result of the study indicated the characteristic influence and persuasive message of "Kita Siap Belajar Optimal!" toward the level of resilience of student's parents of SDN Klender 03 partially and simultaneously. Suggestion to this study, the selection of the models should be reviewed again so the model could be adjusted and recognized by the advertisement's target. The next study suggested to conducting a test for the different sample which have a higher level of school and wider populations.